War and the crisis of youth in Sierra Leone - Peters, Krijn (Cambridge ; New York : Cambridge University Press, 2011)
"The armed conflict in Sierra Leone and the extreme violence of the main rebel faction - the Revolutionary United Front (RUF) - have challenged scholars and members of the international community to come up with explanations. Up to this point, though, conclusions about the nature of the war are mainly drawn from accounts of civilian victims and commentators who had access to only one side of the war. The present study addresses this currently incomplete understanding of the conflict by focusing on the direct experiences and interpretations of protagonists, paying special attention to the hitherto neglected, and often underage, cadres of the RUF. The data presented challenges the widely canvassed notion of the Sierra Leone conflict as a war motivated by 'greed, not grievance'. Rather, it points to a rural crisis expressed in terms of unresolved tensions between landowners and marginalized rural youth, further reinforced and triggered by a collapsing patrimonial state"--
Cover -- Half-title -- Title -- Copyright -- Dedication -- Contents -- Acknowledgements -- Abbreviations -- Introduction -- Tongo in a Time of War -- Three Explanations of the Conflict -- 'New Barbarism, or 'the Apocalyptic View -- Greed, Not Grievance -- State Collapse and a Pent-Up Rebellion of Youth -- Defining the Problem and the Solution -- Chapter Overview -- 1 Voices from the Battlefield: Ex-Combatants' Views on Root Causes of the War and Their Reasons for Participation -- Introduction -- RUF Ex-Combatants -- SLA/AFRC Ex-Combatants -- CDF/Kamajoisia Ex-Combatants -- Discussion -- 2 The Socio-Economic Crisis of Rural Youth -- Introduction -- The Making and Collapse of the State in Sierra Leone -- Slaves and Ex-Slaves -- From Crown Colony to Protectorate -- Political Parties Emerge -- Patrimonial Politics Takes Shape -- APC Oppression -- An Economic Tragedy -- The Patrimonial System Collapses -- The Making and Functioning of Rural Societies in Sierra Leone -- Settler Patterns -- Primitive Accumulation and Domestic Slavery -- Elite Control over Means of Production and Reproduction -- Neither Citizens Nor Subjects: The Political Marginalisation of Youth -- Survival Strategies for Marginalised Youth -- Discussion -- 3 Conflict in Sierra Leone and Recruits to the War -- The Beginning -- Youth in Power -- The Kamajoisia -- And Another Coup -- Towards Final Peace -- 4 The World of the RUF -- Introduction -- Strategies of Bonding -- Conscription -- Loyalty through Punishment and Rewards -- Loyalty through Isolation -- Loyalty to the Leader -- Loyalty through Socialisation -- Meritocratic Principles -- The Interior World of the RUF -- The Bush Camps -- The 'Green Revolution -- Farming in the 'Liberated Zones -- Mining Under the RUF -- Free Education and Health Care -- Rules and Regulations in the RUF -- The RUF's Ideology: 'Drastic Fundamental Change? -- Military and Ideology Training in the RUF -- Mechanisms in the RUF to Monitor the Behaviour of its Fighters and Civilians -- The 'People's Court: Punishment in the RUF -- 5 Malfunctions and Atrocities -- Introduction -- The Erosion of RUF Ideology -- External Factors -- The Liberian Special Forces (19912) -- The Rise of Hunter-Based Civil Defence (19945) -- The AFRC (19979) -- Internal Factors -- Failing Reporting Mechanisms -- Bodyguards -- Native and Non-Native Rebels -- Unpunished Ruthlessness -- Meritocracy and Age -- Liberated Areas and Frontlines -- Terror as Performance: How the RUF Prepared for Battle -- Conclusion -- 6 Cultivating Peace: RUF Ex-Combatants Involvement in Post-War Agricultural Projects -- Introduction -- The Projects -- GTZ Tongo -- NADA Blama -- BANSAL Robol Junction -- RADO Makeni -- KADO Makeni -- Discussion -- 7 Footpaths to Reintegration? Agrarian Solutions for the Reintegration of Ex-Combatants -- A Crisis Denied -- Making Agricultural Packages Central -- The Need for Agricultural Training Projects -- Individual and Collective Farming Opportunities -- Access to Land and Labour -- Towards a New Approach to Agricultural Training -- 8 Conclusion: The RUF as a Rural Underclass Project -- Introduction -- T$
Includes bibliographical references (pages 261-268) and index.
Print version record.
eBooks on EBSCOhost
Keywords: Revolutionary United Front -- History; Revolutionary United Front; Revolutionary United Front; Sierra Leone -- History -- Civil War, 1991-2002 -- Participation, Juvenile; Sierra Leone -- History -- Civil War, 1991-2002 -- Social aspects; Children and war -- Sierra Leone; Youth -- Sierra Leone -- Social conditions; Sierra Leone -- Rural conditions; Rural development -- Sierra Leone; Sierra Leone -- Histoire -- 1991-2002 (Guerre civile) -- Participation des jeunes; Sierra Leone -- Histoire -- 1991-2002 (Guerre civile) -- Aspect social; Enfants et guerre -- Sierra Leone; Jeunesse -- Sierra Leone -- Conditions sociales; Développement rural -- Sierra Leone; HISTORY; Children and war; Military participation -- Juvenile; Rural conditions; Rural development; Social aspects; Youth -- Social conditions; Sierra Leone; Bürgerkrieg in Sierra Leone; Landjugend; Randgruppe; Soziale Situation; Kind; Soldat; Sierra Leone; 1991-2002; Electronic books; History